The Routledge guidebook to Augustine's Confessions - Catherine Conybeare (The Routledge guides to the great books, 2016)
Augustine's Confessions is one of the most significant works of Western culture. Cast as a long, impassioned conversation with God, it is intertwined with passages of life-narrative and with key theological and philosophical insights. It is enduringly popular, and justly so. The Routledge Guidebook to Augustine's Confessions is an engaging introduction to this spiritually creative and intellectually original work. This guidebook is organized by themes: the importance of language; creation and the sensible world; memory, time and the self; the afterlife of the Confessions. Written for readers approaching the Confessions for the first time, this guidebook addresses the literary, philosophical, historical and theological complexities of the work in a clear and accessible way. Excerpts in both Latin and English from this seminal work are included throughout the book to provide a close examination of both the autobiographical and theoretical content within the Confessions.